PENGARUH LINGKUNGAN KERJA, KESEHATAN KERJA, DAN KESELAMATAN KERJA TERHADAP SEMANGAT KERJA KARYAWAN PADA PT PLN (PERSERO) GENTENG - Ririn Windari; Maheni Ika Sari; Haris Hermawan (Growth, 2021)
This research was conducted to see the effect of work environment, occupational health and safety on employee morale at PT PLN (Persero) Genteng . This research was conducted at the office of PT PLN (Persero) Genteng, Banyuwangi Regency, to be precise, all employees totaling 60 people. Sampling was done by using a census technique in which all populations were used as research samples . This is done to increase employee morale as seen from the work environment, work health and work safety. The analysis usedin this research consists of instrument test (validity test and reliability test), multiple linear regression analysis, classical assumption test (normality test, multicoline aritas test, auto correlation test, and heteroscedasticity test), hypothesis test in the form of partial t test and determination coefficient analysis. . The results of multiple linear regression analysis in this study prove that the work environment (0.213), occupational health (0.211), and work safety (0.241) have a significant effect on employee morale.